Psycholinguistic profiling reveals underlying impairments for Greek children with speech disorders. (February 2016) - Geronikou, Eleftheria; Rees, Rachel
This study investigated the possibility that similar speech error patterns in children may arise from different patterns of underlying speech processing difficulties. Four Greek children (aged 4;7–5;6 years) with similar speech output difficulties were assessed with a range of experimental tasks with phonologically matched items in order to profile a selection of the consonants and clusters, with which they experienced production difficulties. To check that the skills and words tested were typically acquired by this age, the tasks were also conducted on a control group of five typically developing children (aged 4;4–5;11 years). Tasks included nonword auditory discrimination, mispronunciation detection, naming, real word repetition and nonword repetition. For the experimental group, comparison of performance across tasks for each consonant or cluster identified different loci of difficulty across children. The findings suggest that this kind of profiling could reveal underlying speech processing difficulties, leading to implications for intervention.